Interests and Behaviors in Reading English Literacy of State Religious College Students - Anita Anita; M. Furqon Adli (Pusat Publikasi Ilmiah UIN Fatmawati Sukarno Bengkulu, 2023)
The study aims to determine interests and behaviors in reading English literacy, as well as the obstacles faced by students in reading English literature in prospective language teacher students at Islamic Higher Education. The study uses quantitative survey design to collect the primary data by using purposive sampling as 200 pre-service teachers. The results showed that students' interest and reading habits in English literature were quite good. This was demonstrated by the fact that most participants (52%) liked reading English literature, while 48% said they were 'ordinary' and 'didn't like' reading English literature. However, the time spent by participants reading English literature was still in the small category, namely less than one hour per day (67%). The dominant English literature accessed by participants was fictional essays in online form (29.5%) and scientific articles supporting courses in printed form (48.5%). Researchers recommend that students' interest and reading habits in English literature need to be improved, one of which is by integrating English literature reading activities into lecture activities and establishing literacy programs as student extracurricular activities.